Supercapacitor like behavior in nano-sized, amorphous mixed poly-anion cathode materials for high power density lithium and other alkali-metal ion batteries. (1st April 2020) - Mitra, Arijit; Jena, Sambedan; Majumder, Subhasish B.; Das, Siddhartha
Abstract: In this manuscript, we report a new mixed poly-anionic framework based material as a cathode for lithium-ion batteries which is having an amorphous structure as compared to traditional crystalline nature of cathode materials, with a chemical formula of Na2 Fe(PO4 ) (CO3 ). The amorphous mixed poly-anion cathode is synthesized using one-pot microwave hydrothermal synthesis technique, which is a faster and cheaper technique as compared to the traditional techniques of forming amorphous structures. The particle size of the material lies in the nano-regime, with a particle size distribution in the range of 10–80 nm. The amorphous structure, combined with the small particle size, shows excellent electrochemical properties as lithium-ion battery cathode. The half-cells are able to charge at constant specific current of 1 A g -1 (∼10C rate), and deliver an energy density of ∼150Whkg −1 at a specific discharge current of 50 mAg −1, consistently without fading. The cell is able to charge to ∼85% of its theoretical capacity in under 7 min with CC-CV charging scheme, and deliver the capacity at 50 mAg −1 specific discharge current (∼0.5C) with an efficiency >97% for ∼150 cycles, with ∼100% capacity retention. The high energy density and the anomalous charge-discharge profile of the material make it extremely suitable for next-generation supercapacitors as well. Graphical abstract: Image 1